2003
DOI: 10.1111/1467-839x.t01-1-00007
|View full text |Cite
|
Sign up to set email alerts
|

Chinese values in Singapore: Traditional and modern

Abstract: A series of three studies was conducted to test the internal structure of the Chinese value hierarchy (CVH) in Singapore. Study 1 identified the empirically best-fit model with six factors: Prudence, Industry, Civic-Harmony, Moral Development, Social Power and Moderation. Relative magnitudes and interfactor correlations suggested that these factors could be further grouped into two superordinate clusters: (i) The Modern factor, with significantly higher magnitude, consisted of Prudence, Industry, Civic-Harmony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 10 publications
4
49
0
Order By: Relevance
“…Recently, some strategic management researchers have started considering the impact of cultures on inter-firm alliance creation; in the international management field, a large number of studies exist on the effect of cultural factors on direct strategic alliances, partnering strategies for joint ventures, and cross-cultural contexts. Studies show that national culture influences firms' models of organization (Hofstede 2005), internal processes and decision-making processes (Rugman, Collinson 2009), strategic choices (Kogut, Singh 1988), performance (Ghamewat 2001) and members' values (Chang et al 2003). Understanding the role of contextual factors like national culture in alliance portfolio formation and its influence on firms' performance in the context of global competition seems to be particularly important in the fast growing and rapidly changing ICT industry.…”
Section: S396mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, some strategic management researchers have started considering the impact of cultures on inter-firm alliance creation; in the international management field, a large number of studies exist on the effect of cultural factors on direct strategic alliances, partnering strategies for joint ventures, and cross-cultural contexts. Studies show that national culture influences firms' models of organization (Hofstede 2005), internal processes and decision-making processes (Rugman, Collinson 2009), strategic choices (Kogut, Singh 1988), performance (Ghamewat 2001) and members' values (Chang et al 2003). Understanding the role of contextual factors like national culture in alliance portfolio formation and its influence on firms' performance in the context of global competition seems to be particularly important in the fast growing and rapidly changing ICT industry.…”
Section: S396mentioning
confidence: 99%
“…Globalization processes do not change the values and beliefs across countries: Strong traditional values, such as group solidarity, interpersonal harmony, and paternalism, can coexist with modern values of individual achievement and competition (Chang et al 2003;Zhang et al 2003). It is worth noting that the top-down effects on cultural change are also moderated by culture itself (Inglehart, Baker 2000).…”
Section: National Culture Organizational Model and Alliance Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…This program was integrated into the education system to help Singaporeans acquire and maintain their respective cultural history and values through their mother tongue whilst sharing a national identity (Chua, 2009). Its impact can be observed in a comparison of Chinese and English speaking students which found that those students who preferred speaking in their mother tongue were more acculturated with traditional Chinese values (Chang, Wong, & Koh, 2003). The bilingual education system works alongside familial nurturing to engender different cultural values learned by each ethnic group.…”
Section: The Singapore Contextmentioning
confidence: 99%
“…In the above section, we discussed Chang, Wong, Teo, and Fam (1997), Chang, Wong, and Teo (2000), Chang, Wong, and Koh (2003), Liao, Shi, and Wong (2012), Liao and Wong (2008, Moslehpour, Wong, Aulia, and Pham (2017), Moslehpour, Wong, Lin, and Huyen (2017). For further detailed analysis, the interested reader is referred to Wong (2016a, c, 2017a, b).…”
Section: Applications In Psychology Marketing and Managementmentioning
confidence: 99%